Frequency of HLA-B27 in Patients With Conductive System Disturbance and Implanted Permanent Pacemaker in Iran - Sayah, Sima; Ebrahimi, Morteza; Piroozmand, Poorya (International Journal of Cardiovascular Practice, 2017)
Introduction: HLA-B27 is considered as one of the causes of heart conductive disorders. We studied the frequency of HLA-B27 among Iranian patients who had undergone permanent pacemaker implantation.Methods: This descriptive and analytical study was performed among patients who underwent permanent pacemaker implantation. The questionnaire contains demographic data, underling diseases, and history of heart disease or heart surgery. The type of conductive heart disorder was mentioned there, too. We determined the regurgitation of aorta valve and its severity. Finally, HLA-B27 was accessed. All the data was entered in SPSS software and analyzed.Results: From a total of 103 patients entered in this study, only 6 (5.8%) were HLAB-27 positive. The disturbance of conductive heart disorders based on the HLA-B27 positive or negative patients was not statistically different. Patients with HLA-B27 mostly had regurgitation of the aorta valve.Conclusions: We concluded that the frequency of positive HLA-B27 genotype in patients with permanent pacemakers did not have any significant difference with the ones with negative HLA-B27 genotype. However; this genotype was associated with regurgitation of the aorta valve.